WISATA KEARIFAN LOKAL DAN IMPLIKASI TERHADAP KETAHANAN BUDAYA : Studi di Obyek Wisata Gunung Tidar Magelang - Supriyono, Tjatur; Silitonga, Franky; Widayanti, Windy Kartika Putri (JURNAL DWIJA KUSUMA, 2024)
Mount Tidar is known as the "Pakuning of Java," standing at an elevation of 503 meters above sea level. It is a tourist attraction that remains pristine, as it is a forest predominantly covered with pine trees. This tourist site has preserved local wisdom that has developed in the community, namely the tombs of Kyai Semar, Kyai Sepanjang, and also the tomb of Syeh Subakir. Mount Tidar is inseparable from military education (AKMIL) as the Candradimuka crater that produces warrior officers of the Sapta Marga. The method used in this research is a qualitative approach involving interviews with local residents and stakeholders from the tourism area, including government officials and managers, to gather data. The collected data is then rechecked and refined through triangulation to obtain reliable results. The results of this research indicate that the local residents possess knowledge of the culture and local wisdom that has developed in the tourist site. Meanwhile, it is necessary for stakeholders to emphasize that the culture and local wisdom should be incorporated into the curriculum based on local wisdom. In addition, there is a need for training for tour guides to preserve history, the evolving culture, and local wisdom so that they continue to develop without being influenced by new cultures that have emerged recently. Residents also suggest the need for facilities and infrastructure to support the tourist attraction, one of which is the expansion of parking areas.